COMMERCIAL FISHING AND MARKETING OF HILSA SHAD TENUALOSA ILISHA(HAMILTON-BUCHANON, 1822) IN BASRAH -SOUTHERN IRAQ - ilisha, Tenualosa (Emirates Journal of Food and Agriculture, 2011)
A field and reference study was conduct for the fishing and marketing operations of Hilsa Shad Tenualosa ilisha in the commercial center in Basrah. The data collected from fishermen and retailsalesmen and compared with the fishing data in the previous years. Fishing production divided into three periods: 1965-1974, 1990-2002 and 2003-2007. The highest Hilsa Shad fishery production was in the 2002 (nearly 12000 tons) with total fishery production of 22918 ton. The Hilsa Shad accounted for 48% of the total fishery production during 1965-1974, which was the highest, compared to the second and third periods (28% and 12% respectively). There might be many reasons for this temporal change over fishing for the previous years, pollution and no regulations to protect the marine fish stock. Marketing of Hilsa Shad occurred mostly in Basrah Governorate with prices ranging between 1.5 and 2 /fish in 1965-1974 and 4- 6 /fish in the recent years for a medium sized fish (30-35 cm total length).